Challenges to cooperative societies: implementation of international standards of accounting CPC 01 - Yoshitake, Mariano; Santana Fraga, Marinette; Tinoco, João Eduardo Prudêncio (REBRAE, 2016)
The objective of this study is to identify the main barriers in the International Standard Application of the "Impairment of Assets" (CPC 01) which from the 2010 financial year, will have on cooperative societies. We used exploratory and descriptive research with a qualitative approach, using literature and document analysis. The exploratory and descriptive research, according to Gil (2002), searches for the initial understanding of a given phenomenon, in this case, cooperatives in general. The results show that although the standard allows a number of different methods to be used in determining its various assumptions, little concrete guidance is passed to accountants in applying these methods. Coupled with the natural complexity of introducing a concept and accounting regulations, must consider the lack of skilled labor in Brazil to define and implement complex premises, sensitive and with a high degree of judgment involved. That said, it is expected that the definition and application of these assumptions should be supported by independent experts and widely discussed among managers of cooperatives. We conclude that the cooperative societies, in particular, with little experience in Accounting, will face difficulties and serious problems in the implementation of accounting pronouncement CPC 01.